Efficient and stereodivergent synthesis of unsaturated acyclic fragments bearing contiguous stereogenic elements. Issue 11 (November 2018) - Bruffaerts, Jeffrey; Pierrot, David; Marek, Ilan
Abstract Synthetic organic strategies that enable the catalytic and rapid assembly of a large array of organic compounds that possess multiple stereocentres in acyclic systems are somewhat rare, especially when it comes to reaching today's high standards of efficiency and selectivity. In particular, the catalytic preparation of a three-dimensional molecular layout of a simple acyclic hydrocarbon skeleton that possesses several stereocentres from simple and readily available reagents still represents a vastly uncharted domain. Here we report a rapid, modular, stereodivergent and diversity-oriented unified strategy to construct acyclic molecular frameworks that bear up to four contiguous and congested stereogenic elements, with remarkably high levels of stereocontrol and in only three catalytic steps from commercially available alkynes. A regio- and diastereoselective catalytic Heck migratory insertion reaction of alkenylcyclopropyl carbinols that merges selective C–C bond cleavage of a cyclopropane represents the key step. A rapid, modular, stereodivergent and diversity-oriented strategy for constructing acyclic molecular frameworks bearing up to four contiguous and congested stereogenic elements has been developed. This approach can yield the target compounds with remarkably high levels of stereocontrol in only three catalytic steps from commercially available alkynes.